PATTERNS OF LOCAL AND GENERAL IMMUNITY AMONG CHILDREN SUFFERING FROM COMMON ILLNESSES ACCOMPLISHED BY LYMPHADENOPATHIES - N. N. Popov; A. N. Savvo; E. A. Romanova (Медицинская иммунология)
Abstract. We have studied some features of immune system in children with common episodes of acute respiratory infections accompanied by lymphadenopathies (LAP). Among this cohort of the patients, a decrease in general immune reactions was revealed, accomplished by polyclonal activation of distinct lymphocyte subpopulations. Certain immune changes have been discerned in children with common infections accompanied by a LAP syndrome, such as an increased ratios of T- and B-lymphocytes carrying CD69 and CD25 activation molecules, a CD71 marker typical for proliferating cells, NKT-cells positive for CD3, CD56, CD8 with high cytokine-producing potential, as well as increased rates of spontaneous blast transformation of lymphocytes, both in course of the disease, and following recovery of the children.